SAT0219 Prevalence and predictive role of traditional cardiovascular risk factors in a cohort of sjögren's syndrome patients. (23rd January 2014) - Bartoloni, E.; Alunno, A.; Baldini, C.; Priori, R.; Quartuccio, L.; Carubbi, F.; Colafrancesco, S.; Maset, M.; Bombardieri, S.; Valesini, G.; De Vita, S.; Giacomelli, R.; et al.
Abstract : Background: Although evidence of precocious cardiovascular (CV) involvement in primary Sjögren's syndrome (SS) is lacking, young SS women display signs of subclinical atherosclerosis. Among disease-related immunologic features, leukopenia and anti-SSA appear to correlate with subclinical atherosclerotic damage (1, 2). However, long-term occurrence of CV events and traditional risk factors role for CV disease in these patients have not been clarified (3). Objectives: Evaluate prevalence and clinical significance of traditional CV risk factors in a cohort of primary SS patients. Methods: Data from 1, 170 SS patients were retrospectively analyzed. Following CV risk factors were considered: smoking (current/previous), hypercholesterolemia (total cholesterol serum level >240 mg/dl), hypertriglyceridemia (serum triglyceride level >150 mg/dl), high-density lipoprotein cholesterol (HDL-c) level (reduced <40 mg/dl, normal: 40-60 mg/dl, increased >60 mg/dl), low- density lipoprotein cholesterol (LDL-c) level (reduced <130 mg/dl; normal: 130-160 mg/dl; increased >160 mg/dl), hypertension (physician diagnosis and/or active anti-hypertensive therapy), diabetes mellitus (active diabetes therapy and/or ≥2 fasting glycemia >126 mg/dl), obesity (according to body mass index). CV events included: fatal/non fatal ischemic myocardial infarction (IMA), stroke, transient ischemic attack (TIA), angina, heart failure (HF), peripheral arterial disease (PAD). Multivariate analysis was performed to compare clinical and immunologic SS features according to CV risk factors number (≤2 or >2). Results: Complete data from 711 (693 female, 18 men) patients were available. A total of 605 (589 female and 16 men, mean age at diagnosis 51.3±13.8 years) and 106 (104 female and 2 men, mean age at diagnosis 53.9±11 years) patients displayed ≤2 and >2 CV risk factors, respectively. Hypercholesterolemia was the most prevalent CV risk factor (33%), followed by hypertension (30%), increased LDL-c (18%), obesity (11%), hypertriglyceridemia (9%), reduced HDL-c (8%), past smoking (7%), diabetes mellitus (3%) and current smoking (2%). Angina and HF were reported in 1% and IMA, stroke and TIA in <1% of patients. No patient reported PAD. At multivariate analysis, presence >2 CV risk factors was significantly associated with older age, lung involvement, leukopenia and circulating anti-SSA/Ro. Patients >2 CV risk factors received immunosuppressive therapy more frequently than the other group. Conclusions: Hypercholesterolemia is the most prevalent traditional CV risk factors in a SS cohort. Patients with more CV risk factors may be at increased risk of extra-glandular involvement and to require more often immunosuppressive therapy, suggesting that high disease activity may be associated with an unfavorable CV profile. Interestingly, persistent leukopenia and circulating anti-SSA, as already shown in previously reported studies (1, 2), may play a role in the pathogenesis of atherosclerotic damage and consequent CV events in SS. References: Gerli R; Arthritis Care Res 2010;62:712 Vaudo G; Arthritis Rheum 2005;52:3890 Gerli R; Rheumatology 2006;45:1580 Disclosure of Interest: None Declared